Reference pricing systems on the pharmaceutical market - Maximiliane Unsorg (University of Tübingen, Faculty of Economics and Social Sciences, 2018)
Constantly rising expenditures for pharmaceuticals require government intervention in firms' pricing decisions. To this end, reference pricing systems are a frequently employed regulatory mechanism. This paper considers a duopoly market with vertically differentiated firms under different competition types. Starting from the existing literature it can be confirmed that the introduction of a reference price leads to lower equilibrium prices and induces fiercer competition between firms. Further, it can be shown that reference pricing promotes generic usage and leads to an increased market coverage. Hence, an improved provision of medical supply is achieved due to the lower prices and the stimulated demand for drugs. The paper demonstrates that even under the increased demand consumer and insurance expenditures are reduced. The model isolates the mechanisms of reference pricing and shows the effects on the consumer decisions. Lastly, consumer surplus increases when implementing the regulation.
urn:nbn:de:bsz:21-dspace-853790
Keywords: I11; I18; L51; 330; reference pricing; pharmaceutical market; copayment; price cap; price competition; expenditures; consumer surplus